LANGUAGE ATTITUDES AMONG STUDENTS IN MULTILINGUAL EDUCATIONAL SETTINGS: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Juliati Juliati; Helminsyah Helminsyah; Nattapong Srisuk (SENSEI RESEARCH CENTER, 2025)
In a multilingual school the students usually speak more than one language, for example the local language at home and the national language at school. Sometimes the students feel that their local language is not important. This article discusses language attitudes among students in multilingual educational settings. The method used is literature review. The result shows that the attitude of the students is influenced by the school policy, the teacher, and also the family. If the local language is not used at school the students will think that it is not useful. Therefore the school should give more space for all the languages of the students.